A New Software Development Methodology for Clinical Trial Systems. (21st March 2013) - Liu, Li-Min
Abstract : Clinical trials are crucial to modern healthcare industries, and information technologies have been employed to improve the quality of data collected in trials and reduce the overall cost of data processing. While developing software for clinical trials, one needs to take into account the similar patterns shared by all clinical trial software. Such patterns exist because of the unique properties of clinical trials and the rigorous regulations imposed by the government for the reasons of subject safety. Among the existing software development methodologies, none, unfortunately, was built specifically upon these properties and patterns and therefore works sufficiently well. In this paper, the process of clinical trials is reviewed, and the unique properties of clinical trial system development are explained thoroughly. Based on the properties, a new software development methodology is then proposed specifically for developing electronic clinical trial systems. A case study shows that, by adopting the proposed methodology, high-quality software products can be delivered on schedule within budget. With such high-quality software, data collection, management, and analysis can be more efficient, accurate, and inexpensive, which in turn will improve the overall quality of clinical trials.